Note historique sur les effets externes - Laffont, Jean-Jacques (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
AbstractThis historical note describes from Sidgwick on the evolution of the concepts related to the interdependencies of economic agents outside markets. In a first section, we show how the concept of externality introduced by some precursors had later to reemerge from the confuse discussion of "empty boxes". The second sector clarifies the distinction between two avenues of research, the first one associated with pecuniary externalities, the other one associated with technological externalities. Coase's criticisms of Pigouvian policy are developed in section 3. In a last section we gather the main results obtained recently by economic theory in this field. In particular we discuss the difficulties of the creation of artificial markets, the second best approaches often needed in a Pigouvian policy, results of game theory in models with externalities, planning with externalities.